Lower and Upper Bounds of Inequality of Opportunity in Emerging Economies - Paul Hufe; Andreas Peichl; Daniel Weishaar (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Equality of opportunity is an important normative ideal that concerns politicians and the larger public alike. In spite of its wide acceptance, current estimation approaches in the literature suffer from severe data restrictions that lead to biased estimates of inequality of opportunity. These shortcomings are particularly pronounced for emerging economies in which comprehensive household survey data often is unavailable. In this paper, we address these issues by estimating lower and upper bounds of inequality of opportunity for a set of emerging economies. Thereby, we address recent critiques that worry about the prevalence of lower bound estimates and the ensuing scope for downplaying the normative significance of inequality.
Keywords: D31; D63; I32; 330; Equality of opportunity; inequality; emerging economies